2013
DOI: 10.2105/ajph.2013.301631
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision-Making for Cancer Care Among Racial and Ethnic Minorities: A Systematic Review

Abstract: To assess decision making for cancer treatment among racial/ethnic minority patients, we systematically reviewed and synthesized evidence from studies of “shared decision-making,” “cancer,” and “minority groups,” using PubMed, PsycInfo, CINAHL, and EMBASE. We identified significant themes that we compared across studies, refined, and organized into a conceptual model. Five major themes emerged: treatment decision-making, patient factors, family and important others, community, and provider factors. Thematic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
158
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(168 citation statements)
references
References 64 publications
7
158
3
Order By: Relevance
“…HCPs, which includes nurses, should take the cultural context of "washing" practices into consideration, to help bridge the health care divide, which could provide opportunities for education and clarification. Shared decision-making would involve a discussion of preferences by both women and their HCPs, and arriving at mutually agreed-upon decisions (Mead et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…HCPs, which includes nurses, should take the cultural context of "washing" practices into consideration, to help bridge the health care divide, which could provide opportunities for education and clarification. Shared decision-making would involve a discussion of preferences by both women and their HCPs, and arriving at mutually agreed-upon decisions (Mead et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…First, overuse of mHealth apps in the SDM context may undermine the quality of the patient–physician relationship if healthcare providers use them to replace spending time with patients [27]. In addition, in cultures or subcultures where a strong hierarchy of authority makes SDM less likely to take hold in the clinic, a mobile app that challenges the traditional doctor/patient roles is unlikely to change the situation [31]. …”
Section: Perils Of Mhealth In Shared Decision Makingmentioning
confidence: 99%
“…43,44 A systematic review of studies that evaluated racial/ethnic minority groups facing cancer revealed ''individuals' perceptions and preferences for medical decision making cannot be authentically examined outside the context of family and community-and that this may be especially so among ethnic minority patients.'' 45 Preferences and goals for care at the end of life in ethnically diverse populations are understudied. A recent report showed that non-Hispanic black family members were less satisfied with the end-of-life care of their loved one when compared to non-Hispanic white family members.…”
Section: Ethnic and Cultural Differencesmentioning
confidence: 99%